Phenotyping and genotyping in patients with inflammatory bowel disease in a reference center in Colombia - Parra Izquierdo, Viviana (2024)
Introduction: Attempts have been made to identify the genetic factors related to susceptibility to inflammatory bowel disease (IBD), and the current conclusions are in favor of a complex pathology model, without a clear hereditary pattern. Objective: To perform phenotypic and genotypic characterization of patients with IBD in Colombian population and to describe its possible association with predisposition. Materials and methods: case series, 16 patients with IBD according to clinical and pathological criteria, onset of gastrointestinal symptoms after 18 years of age. All had pre-test genetic counseling and family trees of at least three generations were made. Also, genotyping, using a multigene panel that included genes related to IBD and some autoimmune disorders. Finally, a genomic analysis of variants was performed. Results: 9 women and 7 men, with mean age of diagnosis of IBD of 35 years, and gastrointestinal symptoms appearance of 32 years. 11/16 (68.75%) required biological therapy. 10/16 (62.5%) were refractory to standard therapy. 3/16 (18.75%) had positive family history of IBD. 100% cases presented at least one single nucleotide polymorphism related to IBD risk in more than one gene. The genes most related to ulcerative colitis (UC) were CD48, CD6, and TYK2 for UC, and CD6 and ITGAM for Crohn's disease. The most frequent gene was CD6. It was found presence of up to 5 genes in 3/16 (18.75%), 4 in 3/16 (18.75%), and three in 5/16 (31.25%). Conclusion: In IBD there is the presence of genetic variants with associated predisposition, but without confirmed pathogenicity, and whose sum seems to contribute to its pathophysiology.